TO THE THEORY OF CURRENT AND VOLTAGE RESONANCE IN AN RLC OSCILLATOR CIRCUIT (Web of Teachers: Inderscience Research, 2025)
This article is devoted to current and voltage resonances in RLC oscillatory circuits. Particular attention is paid to the theoretical foundations of resonant processes.